2013
DOI: 10.1186/1471-2407-13-252
|View full text |Cite
|
Sign up to set email alerts
|

A new assay for measuring chromosome instability (CIN) and identification of drugs that elevate CIN in cancer cells

Abstract: BackgroundAneuploidy is a feature of most cancer cells that is often accompanied by an elevated rate of chromosome mis-segregation termed chromosome instability (CIN). While CIN can act as a driver of cancer genome evolution and tumor progression, recent findings point to the existence of a threshold level beyond which CIN becomes a barrier to tumor growth and therefore can be exploited therapeutically. Drugs known to increase CIN beyond the therapeutic threshold are currently few in number, and the clinical p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
84
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 38 publications
(88 citation statements)
references
References 35 publications
4
84
0
Order By: Relevance
“…S2B). The fraction of cells without the HAC-GFP in the control line agreed well with previous studies (53). We further confirmed that loss of fluorescence detected by flow cytometry corresponds with HAC loss events using fluorescent in situ hybridization (Fig.…”
Section: Analysis Of the Dcin Gene Catalog Uncovers Multiple Mechanismssupporting
confidence: 92%
See 4 more Smart Citations
“…S2B). The fraction of cells without the HAC-GFP in the control line agreed well with previous studies (53). We further confirmed that loss of fluorescence detected by flow cytometry corresponds with HAC loss events using fluorescent in situ hybridization (Fig.…”
Section: Analysis Of the Dcin Gene Catalog Uncovers Multiple Mechanismssupporting
confidence: 92%
“…Based on this list of dCIN genes, we then chose 20 candidate genes for functional testing in human cells (Table S4). The dCIN phenotype in human cells was examined using a quantitative assay based on a nonessential human artificial chromosome (HAC) (53) (Fig. 3A).…”
Section: Analysis Of the Dcin Gene Catalog Uncovers Multiple Mechanismsmentioning
confidence: 99%
See 3 more Smart Citations